Evolutionary plasticity of AmrZ regulation in Pseudomonas - Baltrus, David A; Dougherty, Kevin; Dias, Beatriz; Murillo, Rachel (PeerJ Preprints, 2016)
amrZ, a master regulator protein conserved across Pseudomonads, can be either a positive or negative regulator of swimming motility depending on the species examined. To better understand plasticity in the regulatory function of AmrZ, we characterized the mode of regulation for this protein for two different motility related phenotypes in P. stutzeri. As in P. syringae, AmrZ functions as a positive regulator of swimming motility within P. stutzeri, which suggests that the functions of this protein with regards to swimming motility have switched at least twice across Pseudomonads. Shifts in mode of regulation cannot be explained by changes in AmrZ sequence alone. We further show that AmrZ acts as a positive regulator of colony spreading within this strain, and that this regulation is at least partially independent of swimming motility. Closer investigation of mechanistic shifts in dual function regulators like AmrZ could provide unique insights into how transcriptional pathways are rewired between closely related species.
Keywords: amrZ; Pseudomonas stutzeri; Swimming Motility; Colony Spreading